2020
DOI: 10.3390/cells9030728
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 Alleviates LPS-Induced IL-1β Production by Suppressing NLRP3 Inflammasome Activation and ROS Production in Trophoblasts

Abstract: Emerging evidence indicates that aberrant maternal inflammation is associated with several pregnancy-related disorders such as preeclampsia, preterm birth, and intrauterine growth restriction. Sirtuin1 (SIRT1), a class III histone deacetylase, is involved in the regulation of various physiopathological processes including cellular inflammation and metabolism. However, the effect of SIRT1 on the placental proinflammatory environment remains to be elucidated. In this study, we investigated the effect of SIRT1 on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 62 publications
6
45
0
Order By: Relevance
“…There is also some evidence that, at least in certain contexts, AMPK can accelerate the proteasomal degradation of TXNIP. AMPK activation may also oppose inflammasome activation via activation of the deacetylase Sirt1, which has been shown to inhibit inflammasome assembly in several types of cells [ 135 , 136 , 137 , 138 , 139 , 140 , 141 ]. Sirt1 activity could be expected to inhibit inflammasome priming by suppressing the transcriptional activity of NF-kappaB, but additional mechanisms may be at play [ 142 , 143 ].…”
Section: Berberine Can Down-regulate Txnip Expressionmentioning
confidence: 99%
“…There is also some evidence that, at least in certain contexts, AMPK can accelerate the proteasomal degradation of TXNIP. AMPK activation may also oppose inflammasome activation via activation of the deacetylase Sirt1, which has been shown to inhibit inflammasome assembly in several types of cells [ 135 , 136 , 137 , 138 , 139 , 140 , 141 ]. Sirt1 activity could be expected to inhibit inflammasome priming by suppressing the transcriptional activity of NF-kappaB, but additional mechanisms may be at play [ 142 , 143 ].…”
Section: Berberine Can Down-regulate Txnip Expressionmentioning
confidence: 99%
“…Under oxidative stress, accumulated reactive oxygen species (ROS) leads to post-translational modifications of FOXO3a, thereby regulating the activity and function of FOXO3a. Park et al (2020) demonstrated that SIRT1 can downregulate ROS and form a complex with FOXO3a in cells, which can improve the ability of FOXO3a to induce cell cycle arrest and promote cell survival. Recent findings have indicated that resveratrol, a plant polyphenolic compound, can enhance SIRT1 and decrease ovarian oxidative stress as well as inhibit phosphorylation of p66Shc, both in vivo and in vitro (Wang et al, 2020).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…6 As one of inflammasomes, nod-like receptor pyrin domain 3 (NLRP3) is a protein complex composed of NLRP3, apoptosis-associated speck-like protein(ASC) and caspase-1 that can be activated by lipopolysaccharide (LPS), which is responsible for regulating inflammatory response. [7][8][9] Then, the activation of inflammasome can activate and cleave caspase-1 to trigger the maturation and secretion of IL-1β and IL-18, thus regulating inflammation. 10 Particularly, it has been shown that NLRP3 exerts an inflammatory role in the development of OA.…”
mentioning
confidence: 99%